System and plenary powers of subjects of administrative legal providing of grant of educational services by establishments of higher education - Sezonova, Olha (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
In the article plenary powers of subjects of imperious plenary powers are considered in the field of the administrative legal providing of activity of establishments of higher education. A home legislation on questions education, that touches functioning of Cabinet of Ministers of Ukraine and other central executive bodies, is analysed. The system of subjects of the administrative legal providing of activity of establishments of higher education is offered.